Treino de familiares por meio da videomodelação para aplicação de programas de ensino em crianças com autismo - D'Orazio, Luiza de Freitas Borges (Universidade Federal de São Carlos, 2024)
Family members of ASD people may experience a high level of overload due to the intense care routine and difficulty in teaching their respective children, which may be aggravated because of the lack of a support network. The present research aimed to evaluate the effects of instructional video modeling and immediate feedback on the accuracy of application of training programs in children’s relatives with ASD. Five-dyads of children-caregivers diagnosed with autism spectrum disorder participated of the study. Two dyads are assisted by SUS in an APAE institution; and three dyads are assisted by a private clinic. There was a multiple-probe experimental design among participants, including baseline, intervention, generalization and follow-up. The choice of training programs was made by evaluating the child's initial repertoire, and three skills teaching programs were chosen to be taught to the family members. The results demonstrated that for four participants the video modeling was enough to teach the application of the preference test, and one familiar needed the immediate feedback to reach the criterion. Two participants reached the learning criterion in the training programs through the video modeling and three participants needed to associate the video modeling and the feedback. The caregivers maintained their performances in the maintenance assessment and generalized the application of strategies with the children, and with a new training program, too. The research was effective for caregivers teaching, proving to be a viable alternative for socially vulnerable populations, in addition to enhancing and benefit the repertoire generalization learned in clinical environment.
Training family through video modeling to appy teaching programs to children with autism
Keywords: Capacitação de cuidadores; Videomodelação instrucional; Ensino por tentativas discretas; Transtorno do Espectro Autista (TEA); Parental training; Instructional video modeling; Discrete trial teaching; Autism spectrum disorder (ASD); CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::PROGRAMACAO DE CONDICOES DE ENSINO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::TREINAMENTO DE PESSOAL